Penggunaan Asesmen Diagnostik Non-Kognitif dalam Mengoptimalkan Keterampilan Berbahasa - annisa, Zuraida jihan; Setiana, Leli Nisfi; Wardani, Oktarina Puspita (EUNOIA (Jurnal Pendidikan Bahasa Indonesia), 2025)
The purpose of this study was to determine the role of using non-cognitive diagnostic assessments in optimizing students' language skills. Through non-cognitive diagnostic assessments, teachers can find out the characteristics of students, so that teachers can develop approaches that are in accordance with the characteristics of students and are able to optimize students' language skills. Language skills include listening, reading, writing, and speaking. This study was completed using a qualitative descriptive method with a case study type. The results of this study are that non-cognitive diagnostic assessments can be used by teachers to optimize language skills by adjusting the learning approach according to the characteristics and needs of students.